13 Optimising the management of patients with cancer pain: development and evaluation of the rapid access multidisciplinary palliative assessment and radiotherapy (rampart) clinic. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Jenks, Andrew; Fenton, Paul; Davis, Carol; Brooks, Charlotte; Clode, Lynsey; Driver, Inga; Cawley, Mark
Abstract : Background: Patients with cancer-induced bone pain often wait weeks to receive palliative radiotherapy treatment and to be assessed by specialist palliative care and allied health services. While waiting, they experience debilitating physical problems and psychological distress. This paper reports on the development and evaluation of RAMPART, a 'one-stop' multidisciplinary clinic at University Hospital Southampton. This innovation has not previously been reported in the UK. Methods: The clinic model involves a single visit and combines assessment by palliative medicine, clinical oncology and allied health professionals, with the planning and delivery of palliative radiotherapy. The intervention also involves signposting, onward referrals and supported self-management of physical, psychological and social concerns. A patient satisfaction questionnaire and Macmillan's Holistic Needs Assessment are performed on the clinic day and repeated one month later. Open response questions are asked on the day and at 1 month. Results: Overall, 87% of patients were very satisfied and 13% were satisfied. Patients' global concern score decreased by 1.9 points, mean score 7.1 (range 4–10) on clinic day to 5.2 (range 2–8) at 1 month. There was a reduction in pain score by 2 points, mean score 6.8 (range 3–10) on clinic day to 4.8 (range 0–8) at 1 month. The RAMPART clinic model successfully reduced the median time from referral to radiotherapy from 22 days in the comparator cohort to 8 days in the RAMPART cohort. Qualitative data findings are that patients felt supported, enlightened, informed and valued by the comprehensive nature of the assessment. Patients felt their symptoms and quality of life had improved. Conclusions: Implementing a multidisciplinary palliative radiotherapy clinic is feasible, valued by patients and effective in reducing pain, other patient concerns and time from referral to treatment. This model helps to bridge the gap between hospital and community services and may be transferrable to other areas.